2004
DOI: 10.2337/diabetes.53.8.2018
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine Regulation of Single Pancreatic β-Cell Survival

Abstract: Function and survival of cells depend in part on the presence of growth factors. We explored the autocrine regulation of insulin and nerve growth factor (NGF) on single adult rat pancreatic ␤-cell survival and hormone secretion. When NGF or insulin signaling were blocked in culture media, cell survival decreased compared with control cells, with apoptosis being the main mechanism of cell death. To further explore the role of glucose in ␤-cell survival, we cultured the cells for 16 h in 2.6 mmol/l glucose and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 35 publications
5
56
0
2
Order By: Relevance
“…Here we present evidence that insulin released by the islets in culture activates Akt in an autocrine manner to mediate islet survival. We demonstrate that treatment with an antiinsulin antibody decreased Akt phosphorylation and induced cell death, similar to findings in dispersed rat islets where treatment with anti-insulin antibody increased the amount of TUNEL (TdT-mediated dUTP-biotin nick end labelling)-positive cells [40]. We also demonstrate that inhibition of insulin reception blocks Akt phosphorylation and leads to cell death.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Here we present evidence that insulin released by the islets in culture activates Akt in an autocrine manner to mediate islet survival. We demonstrate that treatment with an antiinsulin antibody decreased Akt phosphorylation and induced cell death, similar to findings in dispersed rat islets where treatment with anti-insulin antibody increased the amount of TUNEL (TdT-mediated dUTP-biotin nick end labelling)-positive cells [40]. We also demonstrate that inhibition of insulin reception blocks Akt phosphorylation and leads to cell death.…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies have also demonstrated high levels of cell death in dispersed islet cultures [40,44]. One explanation for the increase in cell death upon dispersion of islets into single cells is the loss of contact with the extracellular matrix (ECM), which is mediated by the integrin receptor family.…”
Section: Discussionmentioning
confidence: 99%
“…Because insulin is an HNF-1alpha target gene [9,10] and has been implicated in autocrine survival signalling in insulin-secreting cells [33][34][35], we next determined whether apoptosis activation by DN-HNF-1alpha was paralleled by changes in Ins1 gene transcription. Quantitative PCR analysis of Ins1 mRNA expression demonstrated a rapid and prominent downregulation of Ins1 mRNA expression after the induction of DN-HNF-1alpha (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This is due to defects in nutrient-secretion coupling and ATP production [6,9,10]. Insulin release serves as an important autocrine survival signal for the pancreatic beta cells [33,35]. It also activates Ins1 gene transcription via the insulin receptor/PI-3K/p70 S6 kinase pathway [34].…”
Section: Discussionmentioning
confidence: 99%
“…The dynamic changes in the pancreas during progression of β cell death raise certain questions regarding potential autocrine regulatory effects of insulin on β cells (Navarro-Tableros et al 2004). In general, insulin acts as a growth factor that plays an antiapoptotic role and protects cells from death through activation of the PI3-kinase and ERK signaling pathways (Muller et al 2006, Jensen & De Meyts 2009, and insulin therapy can protect β cells from deterioration (Del Parigi 2008).…”
Section: Introductionmentioning
confidence: 99%